Management of the Axilla in the Era of Breast Cancer Heterogeneity - de Meric de Bellefon, Maïlys; Lemanski, Claire; Ducteil, Angélique; Fenoglietto, Pascal; Azria, David; Bourgier, Celine (Frontiers in Oncology, 2018)
Systemic cancer therapies take into account breast cancer (BC) heterogeneity by targeting pathways specifically involved in some BC subtypes. On the other hand, BC intrinsic radiosensitivity is poorly understood and studied. Hence, radiotherapy personalization in BC is still “work in progress”. In this review, we will summarize the existing data on the management of axillary lymph nodes in BC, the impact of BC radiotherapy on axillary management, the indications for axillary radiotherapy, and biomarkers to predict patients’ outcome (tumor control and late toxicities) after axillary irradiation.